ANTIBIOTIC RESISTANCE PROFILING OF DAIRY WASTEWATER DEGRADING NATIVE EFFICIENT MICROBIAL ISOLATES - Bhardwaj, Anupama; Singh, Jagtar; Chaman, Sonia; Joshi, Amit (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this study is to make sure biotreatment process used for treatment of dairy wastewater (DWW) is safe for human and its surrounding environment; microbes were evaluated for their antibiotic resistance profile against commonly prescribed antibiotics. Methods: Microbes were isolated using spread plating and streaking method and used to treat DWW. Reduction in organic load in DWW was determined by comparing physicochemical parameters (PCP) of DWW before and after treatment process. After selection of efficient microbial isolates, they were evaluated for their antibiotic resistance profile using antibiotic disc diffusion method. Results: In this work, 53 microbes were isolated from DWW, and these microbial isolates were screened for DWW degradation capacity by analyzing PCP. Four microbial isolates E3, E5, E11 (bacterial isolates) and F5 (fungal isolate) showed highest reduction in chemical oxygen demand (COD), biological oxygen demand (BOD), and dissolved oxygen (DO) were selected for profound degradation of DWW under optimized conditions. Efficient four microbial isolates individually performed better under anaerobic conditions by showing maximum reduction 84%, 75%, and 77% in COD, BOD, and DO, respectively. After 72 hrs of antibiotic susceptibility testing, E3 strain had shown 100%, E5 90%, E11 70%, and F5 80% susceptibility to antibiotics. Conclusion: The present study concluded that four microbial isolates had the potential of reducing the organic load of DWW along with lessor or negligible adverse effect on human or its surrounding environment and they appear to be most promising strains for treatment of DWW. Â 